Analisis Pelanggaran Kesantunan Berbahasa pada Transaksi Jual-Beli di Pasar Tradisional Kehewanan Samarinda - Ramadhany, Muhammad Alief; Mulawarman, Widyatmike Gede; Rijal, Syamsul (Universitas Mulawarman, 2018)
In the interactions carried out by traders and buyers in the process of buying and selling transactions in the Samarinda Animal Traditional Market, there are speeches that violate the principle of politeness in language. This has prompted researchers to analyze language politeness in the Samarinda Animal Traditional Market. This study aims to describe the level of politeness in the use of community language in the Samarinda Veterinary Traditional Market and describe the violation of the politeness principle spoken by the Samarinda Animal Market community. This study uses a qualitative method. Data collection techniques in this study are tapping techniques, listening techniques, recording techniques and note-taking techniques. The data analysis technique uses a pragmatic equivalent technique. The data in this study are the speeches of traders and buyers at the Samarinda Animal Traditional Market which violate the politeness principle and the politeness scale proposed by Leech. The results of the analysis of the analysis of language politeness violations in buying and selling transactions in the traditional animal market of Samarinda in terms of politeness resulted in an analysis of the Leech politeness scale consisting of cost benefits or the scale of loss and gain, optionality scale or scale of choice, and indirectness scale or indirectness scale. This study also resulted in violations of Leech's six politeness maxims which consist of the maxim of wisdom, the maxim of generosity, the maxim of acceptance, the maxim of humility, the maxim of agreement and the maxim of sympathy